The Effect of Buteyko Breathing Technique in Improving Cardiorespiratory Endurance - Fahrizal, Dani; Santoso, Totok Budi (Universitas Muhammadiyah Surakarta, 2017)
Cardiorespiratory endurance is one of the main aspects required in sports. Cardiorespiratory endurance is influenced by the function of cardiorespiratory system and body oxygenation system. Improving body oxygenation system is just as important as improving cardiorespiratory system to achieve a higher cardiorespiratory endurance. Performing a strenuous activity requires more oxygen to produce the energy. Ironically, our body adapts to a strenuous activity by increasing number of ventilation rate (hyperventilation), which leads to a decreased efficiency of body oxygenation process. Hyper-ventilation reduces carbon dioxide levels by exhaling more carbon dioxide instead of producing it. The carbon dioxide has a main role in maintaining acid-base balance. Altered pH balance causes less oxygen to be released into the tissues. Buteyko Breathing Technique is one of many breathing exercises aimed at improving body oxygenation system. It focuses on decreasing number of ventilation rate and increasing carbon dioxide levels to optimize body oxygenation process. The purpose of this research was to determine the effects of Buteyko Breathing Technique in improving cardiorespiratory endurance. 22 males aged 15-17 were involved to fulfill the objective of the study. This research used parametric test to analyze the data and to observe significant differences in VO2 max improvement between the two groups.